2008
DOI: 10.1590/s0104-11692008000100003
|View full text |Cite
|
Sign up to set email alerts
|

Between freedom and reclusion: social support as a quality-of-life component in the family caregiver-dependent person binomial

Abstract: This is a qualitative study which uses Grounded Theory as its methodological framework and Symbolic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
23

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 11 publications
3
21
0
23
Order By: Relevance
“…An interesting fact reported in the literature [14][15] is that in many situations the average age of caregivers, usually close to or the same as the elderly, or are elderly independent youth caring for the elderly dependent. In this context, our results corroborate other studies, since 10,14,16,18,[20][21][22] also identified an average age of caregivers over 50 years old. This could be explained, at least in part, to be, in many cases, the caregiver spouse.…”
Section: Methodssupporting
confidence: 91%
“…An interesting fact reported in the literature [14][15] is that in many situations the average age of caregivers, usually close to or the same as the elderly, or are elderly independent youth caring for the elderly dependent. In this context, our results corroborate other studies, since 10,14,16,18,[20][21][22] also identified an average age of caregivers over 50 years old. This could be explained, at least in part, to be, in many cases, the caregiver spouse.…”
Section: Methodssupporting
confidence: 91%
“…This change may result from the perception of waning support from one's social network or from inadequate seeking or accepting of help from others when needed. Our results provide strong support for efforts by hospices to continue to develop and improve interventions that help caregivers utilize coping strategies, such as seeking social support to help maintain their quality of life, a technique that is useful for caregivers of non-terminal and terminal patients alike (Bocchi & Angelo, 2008;Raleigh et al, 2006). Decreased emotional quality of life is likely partially attributable to impending loss of a loved one and the probable deteriorating condition of the patient.…”
Section: Discussionmentioning
confidence: 54%
“…another area, each is a unique contributor to overall quality of life (Bocchi & Angelo, 2008). An essential feature of the construct of quality of life is also that it is a subjective judgment of well-being rather than an externally imposed measure (Bernhard, Lowy, Mathys, Herrmann, & Hurny, 2003).…”
mentioning
confidence: 99%
“…Bocchi and Angelo [24] highlight the importance of support from the health team and also to family caregivers, not just for the patient, due to this important role in the routine of the patient.…”
Section: Discussionmentioning
confidence: 99%